Pemanfaatan Pengalaman Simulasi Manajemen dan Roleplayer Facebook terhadap Peningkatan Keterampilan Desain Grafis - Damayanti, Kristya; Rohim, Salma Salseira Osa (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Analyzing Facebook roleplayer management simulation on skills towards potential and challenges in an inclusive and productive online community. This study uses a descriptive quantitative approach. The population in this study took from participants or users of the Facebook roleplayer community. The number of research samples was 100 respondents, using a data collection method through a questionnaire (Google Form). The results of the study using the multiple linear regression data analysis method showed that the results of the F test were f count of 511,940 with a significance of 0.001 which means that Facebook roleplayers simultaneously affect user satisfaction in soft skill training. The results of the T test showed that t count was 7,521 and 9,999 with a significance level of 0.001. This shows that the Null Hypothesis (H0) is rejected where it has no effect and the Alternative Hypothesis (H1) is accepted where it has an effect on variable Y. The results of the determination test showed an adjusted r square of 0.912 which means that Facebook management and roleplayer simulations simultaneously affect user satisfaction in soft skill training by 91.2% and the rest is influenced by other independent variables by 8.8%. This conclusion shows that the better the influence of Facebook management simulation and roleplayer, the higher the user satisfaction with soft skills training.